Wave Decay by Submerged Rigid Vegetation Under Orthogonal Wave‐Current Conditions - Zichen Xu; Jiarui Lei (Geophysical Research Letters)
Abstract Coastal vegetation has drawn significant attention as a nature‐based solution due to its role in wave attenuation. While the wave energy decay by vegetation has been studied under pure‐wave and co‐directional wave‐current conditions, little research has focused on orthogonal wave‐current conditions, which represent propagating waves and longshore currents in natural coastal environments. An analytical model is derived that incorporates various input parameters, including current‐to‐wave velocity ratio, wave height, wave period, water depth, and vegetation properties, to describe wave decay by rigid submerged vegetation under orthogonal wave‐current conditions. Force experienced by individual cylinders was measured, revealing that the drag coefficient of waves is applicable to orthogonal wave‐current conditions. Wave heights were measured along vegetation patches. The presence of an orthogonal current significantly enhanced wave decay by vegetation. The findings of this study underscore the more complicated orthogonal wave‐current conditions and provide valuable insights for future coastal protection strategies incorporating nature‐based solutions.